2002
DOI: 10.1128/jcm.40.12.4797-4799.2002
|View full text |Cite
|
Sign up to set email alerts
|

Rotavirus Gastroenteritis and Central Nervous System (CNS) Infection: Characterization of the VP7 and VP4 Genes of Rotavirus Strains Isolated from Paired Fecal and Cerebrospinal Fluid Samples from a Child with CNS Disease

Abstract: Rotavirus RNA was detected in the cerebrospinal fluid (CSF) of a child with central nervous system disease symptoms associated with rotavirus gastroenteritis. The rotavirus isolates from the fecal and CSF samples were genotyped as G1P [8]. Sequence analysis of the VP7 and VP4 proteins derived from the fecal and CSF samples were remarkably similar to each other and to G1P[8] rotavirus strains commonly circulating in the community and associated with gastroenteritis. CASE REPORTA 22-month-old previously healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
0
3

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 23 publications
2
39
0
3
Order By: Relevance
“…Rotavirus has been detected in cerebral spinal fluid (35,45,58,61,85), liver and kidney (28), extraintestinal lymphoid tissue (12), and the sera of infected children and animals (9,81). By in situ reverse transcription-PCR, rotavirus was also found in the heart, where it was mainly localized to endothelial cells (53).…”
Section: Discussionmentioning
confidence: 99%
“…Rotavirus has been detected in cerebral spinal fluid (35,45,58,61,85), liver and kidney (28), extraintestinal lymphoid tissue (12), and the sera of infected children and animals (9,81). By in situ reverse transcription-PCR, rotavirus was also found in the heart, where it was mainly localized to endothelial cells (53).…”
Section: Discussionmentioning
confidence: 99%
“…In humans, infectious rotavirus was detected in the liver and kidneys of children with severe combined immunodeficiency and rotavirus particles were seen in a liver abscess (28,34,72). Rotavirus antigen and/or RNA was detected in the serum, central nervous system, lungs, liver, kidneys, heart, spleen, testes, bladder, and pancreas of small numbers of children severely ill following rotavirus infection or at autopsy (42,45,46,49,53,54,58,64,67). The presence of serum antigenemia and/or RNA is now considered to be a typical finding during rotavirus infection in children (5,7,11,25,69).…”
mentioning
confidence: 99%
“…Initially, it was thought that rotavirus infection was restricted to the gastrointestinal tract. However, the detection of rotavirus proteins or RNA outside the intestine (7,9,16,(18)(19)(20)23) suggested that rotavirus infection is not limited to the intestine. Extraintestinal rotavirus has been attributed to infections with specific rotavirus strains or in children with immunologic defects (14).…”
mentioning
confidence: 99%